THE SCENARIO OF E-LEARNING IN INDIA- CHALLENGES & OPPORTUNITIES (International Journal of Food and Nutritional Sciences, 2022)
Today, technology is developing at a faster rate. As a result of the broad adoption of technology, it is now easier to obtain knowledge and remote learning is a frequent practise. It boosts a person's capacity for learning as well as their abilities in various aspects of novel subject matter. The finest thing is that it allowed them to learn without really encountering the instructor. E-learning is one of the widely used forms of distance education. With the rapid growth of technology, online education has a long way to go. Like many other nations, India is one of the nations that is evolving around innovative technologies. Because of the lightning-fast pace at which technology is advancing, there will inevitably be some shifts in the educational system. A great deal of study is being done to understand the benefits and drawbacks of online education in comparison to traditional classroom instruction. There is a great deal of competition and potential for growth in the Indian market. Internet-based education. We have recognised internet penetration, the low cost of E-learning, the simplicity of doing course, initiative by the government, employer's acknowledgment, and bridging the gap as the important elements that are contributing to the expansion of E- learning. There are a number of factors that are preventing the expansion of the industry, including inadequate digital infrastructure, credibility issues, and the language that is utilised in online education. With 1.3 billion people, India has a large population, and smart technology is being adopted at an exponential rate. Particularly with the use of smart phones, 4G & 5G technologies, fast internet, and other cutting-edge technology. Every day, more and more people are getting dependent on technology. The introduction of the World Wide Web has had a significant impact on Indian society in a variety of ways. For instance, using social media, ordering food online, sending money online, learning online, etc. Even while e-commerce dominates the online economy, e-learning is just behind it. The rise in the number of people using the internet in India prompted the authors of this research to investigate the potential that may arise in the field of education in the years to come. This study adequately illuminates the current situation's E-learning landscape, as well as the difficulties faced and anticipated changes in India.